An adaptive approach for trialling fully automated vehicles in Queensland Australia: A brief report. (September 2019) - Kaye, Sherrie-Anne; Buckley, Lisa; Rakotonirainy, Andry; Delhomme, Patricia
Abstract: Uncertainty of how fully automated vehicles (AVs) will interact with other road users, including vulnerable road users and other manual automated operated vehicles in towns is one major concern with introducing these vehicles. Based on Walker, Rahman, and Cave's (2001) adaptive policymaking model, this paper illustrates how the adaptive approach can be applied to trial fully automated private vehicles. Specifically, the focus is on policy elements which surround consumer acceptance and other road users' acceptability of private AVs. The State of Queensland, Australia was selected as the focus of this paper given that there are no current policies for fully AVs in this country. It is acknowledged, however, that similar frameworks may also be applied outside of Australia. This paper will also briefly discuss legislation barriers for trialling private AVs in Australia, whilst reviewing the regulations which have been introduced to overcome these barriers at an international level. It was concluded that private AV policymaking is required to be flexible in order to keep up with continued advancements in technology, both in Australia and beyond. Highlights: Case study of an adaptive approach for fully AVs in Australia and beyond. Automated vehicle policymaking required to be flexible and adaptable to change. Amendments to current legislation are required to facilitate on-road trials.